2020
DOI: 10.15586/jptcp.v27i2.665
|View full text |Cite
|
Sign up to set email alerts
|

The effects of medication on intraocular pressure in children with attention deficit hyperactivity disorder: A prospective study

Abstract: Attention deficit hyperactivity disorder (ADHD) is one of the most common psychiatric conditions in childhood. Psychopharmacological therapy is an effective treatment for ADHD. In this study, we primarily aim to investigate the effects of psychopharmacological agents on intraocular pressure (IOP) in children with ADHD. The sample included 82 children with ADHD and 36 healthy children aged between 8 and 12 years who were referred to the Department of Child and Adolescent Psychiatry in Hatay State Hospital, Hata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…Various case reports document potential ocular side effects of both stimulants and non-stimulants in patients with ADHD such as accommodation dysfunction, cataracts, mydriasis, cataracts and increased intraocular pressure [ 138 142 ]. Conversely, other authors [ 60 , 143 ] found no relationship between intraocular pressure and treatment with these medications. Stimulants and various non-stimulant medications used to treat ADHD are adrenergic agonizts, and therefore may affect autonomic regulation of various ocular structures [ 144 ].…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Various case reports document potential ocular side effects of both stimulants and non-stimulants in patients with ADHD such as accommodation dysfunction, cataracts, mydriasis, cataracts and increased intraocular pressure [ 138 142 ]. Conversely, other authors [ 60 , 143 ] found no relationship between intraocular pressure and treatment with these medications. Stimulants and various non-stimulant medications used to treat ADHD are adrenergic agonizts, and therefore may affect autonomic regulation of various ocular structures [ 144 ].…”
Section: Discussionmentioning
confidence: 89%
“…Eleven studies analyzing anatomic ocular measures in people with and without ADHD were included in the meta-analyses. Two for axial length [ 24 , 54 ], four for ganglion cell layer thickness [ 55 – 58 ], three for intraocular pressure [ 56 , 59 , 60 ], eight for macular thickness [ 30 , 54 , 56 59 , 61 , 62 ], two for macular volume [ 61 , 62 ] and eight for RNFL thickness [ 30 , 54 – 58 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have investigated the link between MPH and IOP, and no association was found. [ 25 26 27 ] Larrañaga-Fragoso et al . [ 25 ] examined the IOP in children with ADHD receiving MPH and found no IOP changes at 3 or 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…Güvenmez et al . [ 26 ] also found no significant change in IOP before treatment and after 1- and 6-month treatment periods in children with ADHD. Duman et al .…”
Section: Discussionmentioning
confidence: 99%